Children as Next of Kin in Higher Education: An Exploratory Cross-Sectional Study Among Health, Social Care, and Teacher Education Programs - Almendingen K (Dove Medical Press, 2021)
Kari Almendingen,1 Anne Kristine Bergem,2 Bente Sparboe-Nilsen,1 Lisbeth Gravdal Kvarme,1 Jūratė Šaltytė Benth3,4 1Department of Nursing and Health Promotion, Faculty of Health Sciences, OsloMet – Oslo Metropolitan University, Oslo, Norway; 2Centre for Next of Kin and Carers, Stavanger, Norway; 3Institute of Clinical Medicine, Campus Ahus, University of Oslo, Oslo, Norway; 4Health Services Research Unit, Akershus University Hospital, Lørenskog, NorwayCorrespondence: Kari AlmendingenDepartment of Nursing and Health Promotion, Faculty of Health Sciences, OsloMet – Oslo Metropolitan University, Oslo, NorwayEmail kalmendi@oslomet.noIntroduction: Children who are “next of kin” (ie, sick/dying/addicted/imprisoned close relatives) are at increased risk for health consequences. Health professionals in Norway are required by law to help such children, and professional educations should focus on this issue.Aim: To assess the extent to which students attending health, social care, and teacher education felt their uni-professional education and a mandatory interprofessional learning (IPL) course had taught them about children as next of kin. To explore variations in student responses according to age and educational background.Methods: This was a cross-sectional study. Students (n = 2811) completed questionnaires relating to IPL courses delivered in 2019 and 2020 (hybrid case-based learning). Students discussed issues relating to interprofessional collaboration targeting children, young people and their families in small IPL groups.Findings: The response rates ranged from 25.8% to 36.0%. All but 5.2% of the students agreed that it was important to learn about children as next of kin. Although 61.9% reported that their education had not taught about such children, 73.8% had gained increased insight from the IPL course (difference 35.7% 95% CI (29.0; 42.0), p < 0.001). The teacher and child welfare students had gained greater insight than the health and social care students. Significant pre- to post-course increases were found among the physiotherapy (p < 0.001), Mensendieck physiotherapy (p < 0.001), teacher education (p < 0.001), early childhood education (p < 0.001), and teacher education in art and design (p = 0.042) students.Conclusion: Nearly 2/3 reported that they had not been taught about children as next of kin at their own educations, but more than 2/3 had gained greater insight from the IPL course. The health and social care students reported the least gain. Although the law has existed for a decade, the topic of children as next of kin is still omitted from most educational programs.Keywords: children as next of kin, children as relatives, health, social care, teachers, collaboration, interprofessional